THE The Correlation Diet Complience Toward Quality Of Life In Elderly With Hypertension - Witriyani, Witriyani (Sahabat Publikasi Kuu, 2023)
Background: The elderly experienced the descent of the physiological function due to degenerative diseases so that non-infectious diseases are emerging up. One of them is hypertension. One of the efforts to prevent hypertension complication by obedient behavior on the hypertension diet, which is one of the factors that affect one’s quality of life. Quality of life becomes an important indicator for evaluating the results of hypertension treatment. Purpose: The objective of this study is to determine the correlation diet compliance toward quality of life in elderly with hypertension. Methods: This study is a retrospective correlation with cross sectional approach. The population of the study was 851 people. There were 89 respondents which were chosen by Purposive Sampling technique. The instrument which was used in this study is diet compliance of hipertension and quality of life questionnaire (WHOQOL-BREF). The data were analyzed by using chi square test. Results: The result of bivariate analysis with chi square test obtained value equal to 9.365> 3.481 (X2 count> X2 table) and it is also can be seen that the p value equal to 0.002 (p < 0.05). Conclusions: There is correlation diet complience toward quality of life in elderly with hypertension.